1997
DOI: 10.1135/cccc19971159
|View full text |Cite
|
Sign up to set email alerts
|

Humic Substances - Excited States, Quenching by Metal Ions, and Photosensitized Degradation of Chlorophenols

Abstract: Alteration of photochemical properties of humic substances (HS) by the addition of metals abundant in natural waters has been investigated. Excited HS states have been characterized by fluorescence spectra and by laser kinetic spectroscopy. The effect of Cu2+, Fe2+, and Mn2+ has been explained in terms of static quenching of the HS excited states. In agreement with this, the metal ions were found to inhibit HS sensitized photooxidative degradation of chlorophenols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…As shown in Scheme 1, the mechanism of triplet quenching initially involves the formation of encounter complexes between 3 DOM* and metal ions, likely followed by electron transfer and energy transfer within the complex or radiationless transitions to the ground state. 22,30,31 The metal ions with strong DOM binding capacity have a high affinity to the excited triplet states, thereby leading to a strong quenching effect. 29,30 According to the dynamic quenching rate constants of 3 DOM* by metal ions, the theoretical R 1 O 2 values in the presence of metal ions were corrected with eq 7.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Scheme 1, the mechanism of triplet quenching initially involves the formation of encounter complexes between 3 DOM* and metal ions, likely followed by electron transfer and energy transfer within the complex or radiationless transitions to the ground state. 22,30,31 The metal ions with strong DOM binding capacity have a high affinity to the excited triplet states, thereby leading to a strong quenching effect. 29,30 According to the dynamic quenching rate constants of 3 DOM* by metal ions, the theoretical R 1 O 2 values in the presence of metal ions were corrected with eq 7.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…20,21 These metal ions, especially the transition metal ions, readily tend to form complexes with DOM, thereby affecting its photoreactivity. 22 Previous studies showed that the paramagnetic metal ions markedly inhibit the photodegradation of organophosphorus pesticides, chlorophenols, and β-blockers sensitized by HS. 22−24 Accordingly, the co-existent metal ions exhibit a significant impact on the DOM-sensitized photodegradation of organic pollutants.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A lot of compounds chosen among the most pertinent class of pollutants have been photolyzed in conditions relevant to those prevailing in surface waters. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] In many cases, humicmediated phototransformation significantly contributed to the abiotic transformation pathway.…”
Section: Introductionmentioning
confidence: 99%